The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1177/147323000703500315
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Increased the Interleukin-6 to Interleukin-10 Ratio more than Isoflurane after Surgery in Long-term Alcoholic Patients

Abstract: This study investigated the effect of an anaesthetic regimen on the immune response in 40 long-term alcoholic patients undergoing surgery. Patients were randomly allocated to receive either propofol or isoflurane during surgery. Plasma cytokines interleukin (IL)-6 and IL-10 were measured at defined times and rates of post-operative infections were documented. The IL-6/IL-10 ratio significantly increased with propofol compared with isoflurane on day 1 after surgery and the IL-10 level significantly increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…As a negative acute phase protein, Apo A-I initially decreased, while the proinflammatory mediators increased in all the three groups. Like in other studies we observed higher IL-6 concentrations in the immediate postoperative period following propofol anesthesia as compared to inhalational anesthesia [32,33]. Additionally, we observed a failure of cortisol levels to increase in the propofol and solvent groups which may Table 4.…”
Section: Propofolsupporting
confidence: 44%
See 1 more Smart Citation
“…As a negative acute phase protein, Apo A-I initially decreased, while the proinflammatory mediators increased in all the three groups. Like in other studies we observed higher IL-6 concentrations in the immediate postoperative period following propofol anesthesia as compared to inhalational anesthesia [32,33]. Additionally, we observed a failure of cortisol levels to increase in the propofol and solvent groups which may Table 4.…”
Section: Propofolsupporting
confidence: 44%
“…More aggressive surgery would have produced more pronounced effects on the inflammation, both clinically and on the different molecules measured [33]. This limitation is due to our intent to characterize the effects of propofol on inflammation in a very standardized setting.…”
Section: Propofolmentioning
confidence: 99%
“…They linked the use of morphine to decreased cortisol concentrations, decreased rates of nosocomial pneumonia, and shorter hospital ICU lengths of stay in surgical patients undergoing GI surgery. In the other study by von Dossow et al, 49 the use of propofol as a general anesthetic, when compared with isofl urane, was associated with lower intraoperative cortisol concentrations, improved postoperative immune function, and lower rates of ICU-acquired sepsis in surgical patients with AUDs undergoing GI surgery. These data are particularly intriguing for patients undergoing emergency surgery and may provide an additional option to decrease the rate of nosocomial complications in patients with AUDs.…”
Section: Management Of Sedationmentioning
confidence: 99%
“…48 Administration of agents that decrease cortisol production (ie, administration of low-dose alcohol, morphine, and ketoconazole or propofol) is associated with signifi cant reduction in the rate of sepsis as well as hospital ICU length of stay (discussed in more detail under the "Management of Sedation" and "Management of Withdrawal Syndromes" sections). 49 This approach may have implications for managing other circumstances in which AUDs are associated with poor outcomes and should be investigated further.…”
Section: Burn Patientsmentioning
confidence: 99%
See 1 more Smart Citation